The revenge of the words: On language"s historical and autonomous being and its effects on "secularisation" - Vanhoutte, Kristof K. P. (HTS teologiese studies, 2020)
What if language was an autonomous historical being? What if language’s use was not solely dependent on the intentions of the one who speaks? In this text I will test these provocative statements. Specifically, I will investigate whether language’s proclaimed historical independence can be traced in the usage of the concept of ‘secularisation’, and I will try to unveil the consequences of this operation.Contribution: Has Christianity abandoned the public stage in the ‘secularised’ and industrialised world? In this article I intend to demonstrate that this is not the case. The continuous operative presence of Christianity in our socio-political language is used as the model to prove this argument.